Pemanfaatkan Potensi Lokal Melalui Pembuatan Susu Jagung Guna Mencegah Stunting Pada Desa Gejugan - Agus Edi Setiyono; Ngatimun Ngatimun; Titik Musriati (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2020)
Gejugan Village is one of the villages in Probolinggo district on the north coast. Gejugan Village is in the west bordering Klaseman Village and Karangpranti Village, Pajarakan District. Gejugan village has local potential that can be developed from their agricultural produce, namely corn. Corn is an alternative food source that contains many nutrients. But the people here still don't have the knowledge to be able to use it. The Socialization Activity for Making SUJU (Corn Milk) to Prevent Stunting and Utilizing Local Potential is expected to provide more knowledge to the Gejugan community in utilizing existing local potential, especially processing corn into corn milk. Besides having good nutrition, corn milk also has more value in the economy. If it is processed properly and properly, this product can be sold in the market. The socialization of making corn milk was attended by 25 residents of Gejugan Village. Material for making corn milk was given by providing materials and hands-on practice during the event. Participants in the socialization of making corn milk enthusiastically listened to and practiced directly making corn milk during the socialization process. From the results of the socialization, the practiced corn milk resulted in 6 bottles of corn milk measuring 360 ml. Participants listened well and the material presented was well received by all participants present. Keywords: Local Potential, Corn Milk, Stunting